DETERMINAN YANG MEMPENGARUHI PEMBERIAN ASI EKSKLUSIF PADA IBU BEKERJA DI WILAYAH KERJA PUSKESMAS TIGO BALEH KOTA BUKITTINGGI - Debby Yolanda; Sri Hayulita (Universitas Fort De Kock, 2022)
Exclusive breast milk is the best food for baby growth and development at the age of 0-6 months. Given the enormous benefits of exclusive breastfeeding, the Indonesian government targets the coverage of exclusive breastfeeding to be 80%. The purpose of this study was to determine the factors associated with exclusive breastfeeding for working mothers in the Tigo Baleh Health Center Work Area, Bukitinggi City. The factors studied were knowledge, lactation facilities, attitudes, and husband's support. This study is an analytic observational study with a retrospective cross sectional design involving 42 respondents. The sample was taken by purposive sampling technique using a questionnaire. Data analysis used univariate , bivariate and multivariate analysis. The results showed that there was not a relationship between education (p-value 0.128), there was a lactation facilities (p-value 0.001), attitude (p-value 0.006), and husband's support (p-value 0.005) on exclusive breastfeeding for working mothers in the region. Tigo Baleh Public Health Center in Bukitinggi City. Multivariate analysis obtained factors that influence breastfeeding, namely lactation facilities (p-value 0.003) and attitudes (p-value 0.009). It is hoped that there will be an increase in the support of health workers to carry out health promotion, so that when working mothers return to work, these mothers already have preparations to continue to give exclusive breastfeeding so that exclusive breastfeeding for working mothers will increaseExclusive breast milk is the best food for baby growth and development at the age of 0-6 months. Given the enormous benefits of exclusive breastfeeding, the Indonesian government targets the coverage of exclusive breastfeeding to be 80%. The purpose of this study was to determine the factors associated with exclusive breastfeeding for working mothers in the Tigo Baleh Health Center Work Area, Bukitinggi City. The factors studied were knowledge, lactation facilities, attitudes, and husband's support. This study is an analytic observational study with a retrospective cross sectional design involving 42 respondents. The sample was taken by purposive sampling technique using a questionnaire. Data analysis used univariate , bivariate and multivariate analysis. The results showed that there was not a relationship between education (p-value 0.128), there was a lactation facilities (p-value 0.001), attitude (p-value 0.006), and husband's support (p-value 0.005) on exclusive breastfeeding for working mothers in the region. Tigo Baleh Public Health Center in Bukitinggi City. Multivariate analysis obtained factors that influence breastfeeding, namely lactation facilities (p-value 0.003) and attitudes (p-value 0.009). It is hoped that there will be an increase in the support of health workers to carry out health promotion, so that when working mothers return to work, these mothers already have preparations to continue to give exclusive breastfeeding so that exclusive breastfeeding for working mothers will increase